Ingroup Bias in Healthcare Contexts: Israeli-Jewish Perceptions of Arab and Jewish Doctors - Graham, Elliot; Halabi, Samer; Nadler, Arie (Frontiers in Psychology, 2021)
The influence of group membership on perceptions of outgroup members has been extensively studied in various contexts. This research has indicated a strong tendency for ingroup bias – preferring the ingroup over the outgroup. We seek to further expand on the growing literature regarding the effects of group membership within healthcare contexts. Focusing on the Arab-Jewish context in Israel, the present study explored the influence of group membership on Israeli-Jewish participants’ evaluations when exposed to potential malpractice. Specifically, participants (n = 165) read a description of an Israeli-Jewish or Israeli-Arab physician who was either culpable or non-culpable of malpractice. Consistent with our predictions, findings generally indicated more negative evaluations of the Israeli-Arab physician, regardless of objective culpability. We conclude by discussing the study’s limitations and implications.